Riverbank Erosion Along the Vidyadhari River, Gosaba, South 24 Parganas, West Bengal, India with Suitable Embankment Proposal: A Geospatial Investigation - Nayan Dey; Payel Das (CV. Literasi Indonesia, 2023)
India is a country of rivers. Sundarban is the world’s largest deltaic region, which is also part of the Ganga region. Highly populated this region is frequently faced intensive floods. The objective of this paper is to give a notion about the potential embankment zone along the Vidyadhari River. Changes in riverbanks since 1972 have been highlighted through GIS and Remote Sensing Applications. Through this paper, erosional and depositional zones along the Vidyadhari River are also spotted out. The potential embankment zone is measured by the vulnerability analysis based on river bank shifting. The proper embankment technology has also suggested a sustainable embankment along the river Vidyadhari river, which is guided by the Irrigation Department, Government of West Bengal.